Inclusion and Moral Competence. Hypotheses about Two Closely Related Tasks of the School - Reinicke, Martina (ETHICS IN PROGRESS, 2018)
In my article, I will give a short historical overview of inclusion-research. The focus lies on relation between moral and inclusion. I will introduce three branches of inclusion research and deduce my definition of inclusion from it. Inclusion can be understood as a dynamic process of realizing of equal participation on the one hand and of entitlement to diversity on the other hand. That means, inclusion lives from the solution of its immanent conflict- the conflict between equality and diversity. Therefore, I assume that “the ability to solve problems and conflicts on the basis of universal moral principles by means of deliberation and discussion, instead of using violence, deceit and coercion, or more specifically… the ability to judge arguments in regard to their moral quality instead of their opinion-agreement” (Lind 2016) is urgently needed. This ability is an important precondition for realizing inclusion. Following educational theory of morality by Lind and others, it’s not necessary to change the moral attitudes (moral orientation) in persons that are involved in the process of inclusion. It’s more important to improve their inclusive ability and their inclusive behavior. Inclusive behavior means a behavior with which shows recognition of both: of diversity of all as well as of the dignity of each individual. On this theoretical basis, I furthermore want to introduce a little research project carried out by the author in Vocational School Centre. The aim of this project was to improve the inclusive behavior by using the Konstanz Method of Dilemma Discussion®.